A Brief History Of English Education In The Straits Settlements With Reference To The ST. Xavier’s Institution, Penang 1786 To 1955 - Idros, Aini (Universiti Sains Malaysia, 1974)
The complete history of English education has yet to be written. The main topic of my study is to see how far the educational policy of the British Government was applied to local institutions with special reference to the St. Xavier’s Institution, Penang.